2017
DOI: 10.1016/j.fusengdes.2017.02.093
|View full text |Cite
|
Sign up to set email alerts
|

Integration of the state observer RAPTOR in the real-time MARTe framework at RFX-mod

Abstract: The RAPTOR - RApid Plasma Transport simulatOR code is a model-based control-oriented code that predicts Tokamak plasma profile evolution in real-time. One of its key applications is in a state observer, where the real-time predictions are combined with the measurements of the available diagnostics, yielding a complete estimate of the plasma profiles. The state observer RAPTOR is currently installed in the real-time control system of TCV, where it has been originally developed, ASDEX-Upgrade and recently RFX-mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The Nitrogen concentration is deduced from a prescribed Z ef f profile, and the Tungsten density is taken proportional to that of electrons, with a concentration assumed to be low enough not to contribute to electroneutrality. The Porcelli sawtooth model [43] implemented in RAPTOR is used to prevent the safety factor to go far below unity as plasma current diffuses [44]. This plays an important role here due to the contribution of core ohmic current in the mechanism at play.…”
Section: Integrated Modellingmentioning
confidence: 99%
“…The Nitrogen concentration is deduced from a prescribed Z ef f profile, and the Tungsten density is taken proportional to that of electrons, with a concentration assumed to be low enough not to contribute to electroneutrality. The Porcelli sawtooth model [43] implemented in RAPTOR is used to prevent the safety factor to go far below unity as plasma current diffuses [44]. This plays an important role here due to the contribution of core ohmic current in the mechanism at play.…”
Section: Integrated Modellingmentioning
confidence: 99%
“…In [57] it was shown that the CDE coupled to the equilibrium solution is able to reproduce the measured q-profile evolution associated to a sawtooth crash, when sawtooth-induced current relaxation is accounted for by reconnection models [58], and the fast ions contribution is correctly modeled. These reconnection models are already implemented in RAPTOR [59] but were not used in this paper .…”
Section: Limitations Of Current Approach and Outlooksmentioning
confidence: 99%
“…The Scientific Linux 6.7 was selected as OS, since it is supported by JET CODAS, making the compatibility with other installed systems, forcing the Linux Device Driver upgrade to the new kernel version. For the CDAQ software, MARTe framework was selected because: (i) it fulfills all the diagnostics requirements; (ii) it is used in other JET diagnostics; (iii) it is popular in the fusion community by its usage in several machines, which contributes for its continuous development [ [19]- [25]]. Fig.…”
Section: Cdaq System Uniformizationmentioning
confidence: 99%